Juvenile, Prisons, and Justice: How Do Correctional Agencies Provide Legal Assistance for Children in Conflict with The Law? - Anwar, Syaiful; Galih, Mardella (Faculty of Law Universitas Negeri Semarang, 2021)
The Juvenile Justice System in Indonesia has a special feature where a child facing the law in criminal justice must receive special protection by law enforcers. One of them is the Correctional Center which has an important role in providing input from the police, prosecutors and courts as a form of realization of the protection of children's rights. Children who are included in the group whose rules are in the national and international human rights instruments must receive special protection by providing legal assistance and the state must be responsible for the fulfillment of these special rights. The issues raised in this paper are: What is meant by children dealing with the law and what is the form of legal assistance by correctional institutions (BAPAS) for children dealing with the law. The method used in writing this paper is descriptive qualitative analysis using primary legal material data, secondary legal materials, and other literature study materials.